2018
DOI: 10.22271/ortho.2018.v4.i4e.47
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization versus early active mobilization after surgical repair of injured extensor tendon of hand and forearm

Abstract: Background: Extensor tendon injuries are very common injuries in hand & forearm, which inappropriately treated can cause severe lasting impairment of hand function of the patient. After the extensor tendons repair whether to immobilization or to early active mobilization is debatable. Objectives: Compare the two common protocols, immobilization vs. early active mobilization by using a simple static splint after surgical repair of extensor tendon. Method: This prospective randomized study was conducted in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previously, some authors documented the superiority of early active mobilization technique over the immobilization technique. 2,9,10 The most likely explanation of the difference in our findings is the improper compliance of the instructions given to patients who were treated with early active mobilization. Majority of the patients were illiterate and did not follow the teachings and thereby the outcomes effected.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previously, some authors documented the superiority of early active mobilization technique over the immobilization technique. 2,9,10 The most likely explanation of the difference in our findings is the improper compliance of the instructions given to patients who were treated with early active mobilization. Majority of the patients were illiterate and did not follow the teachings and thereby the outcomes effected.…”
Section: Discussionmentioning
confidence: 74%
“…10 The similar study was conducted in Bangladesh also reported that study participants belonged to age group of 21-30 years with male dominance. 2 Other international literature also reported that males were commonly affected by hand injuries. 11,12 Occupational injury was the most common mode of injury in our study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation